(untitled) (EAAE Annual Conference Proceedings, 2023)
Nomad Science proposes the lived displacement of apparatuses of state science, drawing out and connecting knowledge systems. This production schema places architectural questioning as a free journey, aspiring towards a free subjectivity, accumulated through the nomadic search for distant knowledge fields as a creative project, to transform the nomadic into a new new science for architectural doctorates.